1991
DOI: 10.1172/jci114977
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of gallstone formation in women. Effects of exogenous estrogen (Premarin) and dietary cholesterol on hepatic lipid metabolism.

Abstract: Our aim was to define mechanisms whereby conjugated estrogens (Premarin, exogenous estrogen; Ayerst Laboratories, New York) increase the risk of developing cholesterol gallstones and to determine the role, if any, of dietary cholesterol. We studied gallbladder motor function, biliary lipid composition and secretion, cholesterol absorption, cholesterol synthesis and esterification by peripheral blood mononuclear cells, the clearance of chylomicron remnants, and bile acid kinetics in 29 anovulatory women. 13 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
116
2
2

Year Published

1993
1993
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 226 publications
(128 citation statements)
references
References 59 publications
(37 reference statements)
8
116
2
2
Order By: Relevance
“…Among the mechanisms proposed are altered bile acid metabolism, direct effects on intestinal mucosa, and changes in insulin and IGF-I levels (23,27,42). In a study of anovulatory women, bile acid production was lower while they were taking Premarin than when they were not taking Premarin (43). Another speculation is that estrogen is involved in colonic mucosa differentiation and proliferation via the estrogen receptor in the epithelial cells (42,44).…”
Section: Discussionmentioning
confidence: 99%
“…Among the mechanisms proposed are altered bile acid metabolism, direct effects on intestinal mucosa, and changes in insulin and IGF-I levels (23,27,42). In a study of anovulatory women, bile acid production was lower while they were taking Premarin than when they were not taking Premarin (43). Another speculation is that estrogen is involved in colonic mucosa differentiation and proliferation via the estrogen receptor in the epithelial cells (42,44).…”
Section: Discussionmentioning
confidence: 99%
“…The reduced colorectal cancer risk in women has been attributed to physiological, environmental, and behavioural factors (DeCosse et al, 1993). Especially, oestrogen has been suggested to have a protective role in colon carcinogenesis by affecting metabolism of bile acids and serum levels of insulin-like growth hormone levels (Everson et al, 1991;Campagnoli et al, 1993). Transcriptional silencing of the oestrogen receptor gene has been reported in colorectal tumours (Issa et al, 1994) and a metaanalysis of several epidemiological studies of postmenopausal women reported a significant reduction in the risk of colorectal cancers with hormone therapy (Grodstein et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…During pregnancy, gallbladder volume increases and the flow of bile decreases, which are precursors to gallstone formation (Everson et al, , 1991. Moreover, elevated oestrogen levels during pregnancy increase cholesterol content in the bile, contributing to biliary stasis (Braverman et al, 1980;Kern et al, 1982;Everson et al, 1982Everson et al, , 1991Novacek, 2006).…”
mentioning
confidence: 99%
“…During pregnancy, gallbladder volume increases and the flow of bile decreases, which are precursors to gallstone formation (Everson et al, , 1991. Moreover, elevated oestrogen levels during pregnancy increase cholesterol content in the bile, contributing to biliary stasis (Braverman et al, 1980;Kern et al, 1982;Everson et al, 1982Everson et al, , 1991Novacek, 2006). Pregnancy has also been associated with gallbladder cancer (Lambe et al, 1993;LaVecchia et al, 1993;Moerman et al, 1994;Tavani et al, 1996), but the modifying effect of gallstones and the role of other reproductive factors are not clear.…”
mentioning
confidence: 99%